“Ubi Solitudinem Faciunt, Pacem Appellant”. The Criminal Repression of Political Association in the Transition between Fascism and Republic (Italian Review of Legal History, 2020)
The construction of the crime of association, especially of a political nature, in Italy from Unity to the Republic, appears to be the story of the institutional will to create, in a more or less harsh form, a desert. This construction went hand in hand with the growth of the internal social conflict which, not only if organized, had assumed the guise of a concrete danger, according to the state organization, tending to the subversion and overthrow of the order. Then is when the criminal law revealed itself, with all its strength, as an institutional weapon used for maintaining the established order and social peace, as well as a corpus that can be manipulated and interpreted according to the concrete political needs of the state.
Keywords: fascism; transitional justice; political association; subversive association; antinational association; 1930 Penal Code.